Generation of a primary culture of chick embryo enterocytes to evaluate the effects of fumonisin B1 and deoxynivalenol on cell morphology, actin filaments and nuclei - Jacqueline Uribe-Rivera; Maria de Jesús Nava-Ramirez; Saúl Escobedo-Aguirre; Juan Carlos Del Río-García; Samantha Jardón-Xicoténcatl; Carlos Gerardo García-Tovar; Ernesto Ávila-González; Gabriela Gomez-Verduzco (PLoS ONE, 2025)
Fumonisin B1 (FB1) and deoxynivalenol (DON) are among the most impactful mycotoxins affecting poultry production. The negative effects of these mycotoxins on intestinal epithelial morphology and integrity have been previously described. However, cell culture methods using cells from species with different genetic backgrounds have been used to obtain these results. The objective of this work was to evaluate the damage caused by fumonisin B1 (FB1) and deoxynivalenol (DON) on cell morphology, actin filaments and nuclear morphology in primary enterocytes obtained from chick embryos via fluorescence microscopy. The results revealed that FB1 and DON did not induce actin filament depolymerization, and stress fibers remained intact under the concentrations of mycotoxins evaluated. However, the cytoarchitecture was disrupted in treated cells, leading to cell thinning and reduced viability, and this change affected one of the main characteristics of enterocytes, which is their ability to absorb nutrients. Damage to the integrity of the nucleus was also observed until its fragmentation, especially in cells treated with deoxynivalenol (DON). These results provide new insights into the mechanisms of action by which DON and FB1 exert their negative effects on chicken enterocytes, for which there was no previous information.